KRAS G12C Game of Thrones, which direct KRAS inhibitor will claim the iron throne?. (March 2020) - Nagasaka, Misako; Li, Yiwei; Sukari, Ammar; Ou, Sai-Hong Ignatius; Al-Hallak, Mohammed Najeeb; Azmi, Asfar S.
Highlights: Mutations in Kirsten rat sarcoma viral oncogene homolog (KRAS) are common in cancer. KRAS remains a challenging therapeutic target. Recently, several novel compounds against individual KRAS alterations have emerged. Initial activity of AMG 510 and MRTX 849 appears promising in KRAS G12C NSCLC. Single agent and combination studies are ongoing to evaluate their safety and efficacy. Abstract: Mutations in Kirsten rat sarcoma viral oncogene homolog (KRAS) are among the most common aberrations in cancer, including non-small cell lung cancer (NSCLC). The lack of an ideal small molecule binding pocket in the KRAS protein and its high affinity towards the abundance of cellular guanosine triphosphate (GTP) renders the design of specific small molecule drugs challenging. Despite efforts, KRAS remains a challenging therapeutic target. Among the different known mutations; the KRAS G12C (glycine 12 to cysteine) mutation has been considered potentially druggable. Several novel covalent direct inhibitors targeting KRAS G12C with similar covalent binding mechanisms are now in clinical trials. Both AMG 510 from Amgen and MRTX849 from Mirati Therapeutics covalently binds to KRAS G12C at the cysteine at residue 12, keeping KRAS G12C in its inactive GDP-bound state and inhibiting KRAS-dependent signaling. Both inhibitors are being studied as a single agent or as combination with other targets. In addition, two novel KRAS G12C inhibitors JNJ-74699157 and LY3499446 will have entered phase 1 studies by the end of 2019. Given the rapid clinical development of 4 direct covalent KRAS G12C inhibitors within a short period of time, understanding the similarities and differences among these will be important to determine the best treatment option based on tumor specific response (NSCLC versus colorectal carcinoma), potential resistance mechanisms (i.e. anticipated acquired mutation at the cysteine 12 residue) and central nervous system (CNS) activity. Additionally, further investigation evaluating the efficacy and safety of combination therapies with agents such as immune checkpoint inhibitors will be important next steps.